2008
DOI: 10.1155/2008/840374
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Signals Mediating Induction of Long-Term Synaptic Depression in the Entorhinal Cortex

Abstract: The entorhinal cortex receives a large projection from the piriform cortex, and synaptic plasticity in this pathway may affect olfactory processing. In vitro whole cell recordings have been used here to investigate postsynaptic signalling mechanisms that mediate the induction of long-term synaptic depression (LTD) in layer II entorhinal cortex cells. To induce LTD, pairs of pulses, using a 30-millisecond interval, were delivered at 1 Hz for 15 minutes. Induction of LTD was blocked by the NMDA receptor antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
3
5
0
Order By: Relevance
“…Moreover, whereas PPS caused a significant depression of the pEPSP in the presence of vehicle solution (5 min before PPS vs. 37 min after PPS, p < 0.01), it failed to do so in the presence of okadaic acid ( p > 0.2). The failure of LTD development in the presence of okadaic acid, combined with our previous demonstration that the induction of LTD by PPS is dependent on NMDA receptor activation (Thiels et al, 1998), is consistent with previous observations of an effect of this inhibitor on NMDA receptor-dependent LTD in area CA1 or the entorhinal cortex (Xiao et al, 1995; Jouvenceau et al, 2003; Kourrich et al, 2008). Furthermore, it suggests that either one or both of the okadaic acid-sensitive protein phosphatases are necessary for the development of NMDA receptor-dependent LTD.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, whereas PPS caused a significant depression of the pEPSP in the presence of vehicle solution (5 min before PPS vs. 37 min after PPS, p < 0.01), it failed to do so in the presence of okadaic acid ( p > 0.2). The failure of LTD development in the presence of okadaic acid, combined with our previous demonstration that the induction of LTD by PPS is dependent on NMDA receptor activation (Thiels et al, 1998), is consistent with previous observations of an effect of this inhibitor on NMDA receptor-dependent LTD in area CA1 or the entorhinal cortex (Xiao et al, 1995; Jouvenceau et al, 2003; Kourrich et al, 2008). Furthermore, it suggests that either one or both of the okadaic acid-sensitive protein phosphatases are necessary for the development of NMDA receptor-dependent LTD.…”
Section: Resultssupporting
confidence: 92%
“…A number of studies showed that the PP1 and PP2A inhibitor okadaic acid disrupts NMDA receptor-dependent LTD at glutamatergic synapses in hippocampus as well as elsewhere in brain (Mulkey et al, 1993; Kirkwood & Bear, 1994; Morishita et al, 2001; Jouvenceau et al, 2003; Belmeguenai & Hansel, 2005; Kourrich et al, 2008), implicating one or both of these protein phosphatases in activity-dependent modification of synaptic strength. Here we sought to determine the role of each of these two protein phosphatases individually to NMDA receptor-dependent LTD in area CA1 in vivo (Thiels et al, 1998), taking advantage of specific inhibitors of PP1 and PP2A, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10 A , C ). FK506 was active when loaded into the postsynaptic neurons as loading the same concentration of FK506 into neurons of layer 2 of the medial entorhinal cortex completely prevented LTD in synaptic input from layer 1 (not shown), as previously reported ( Kourrich et al 2008 ), indicating that presynaptic calcineurin is involved in the induction of hippocampal t-LTD..
Figure 10. Presynaptic calcineurin is involved in t-LTD at CA3-CA1 synapses.
…”
Section: Resultssupporting
confidence: 80%
“…When okadaic acid was applied internally, it produces a slowly developing attenuation in response to 0.05 Hz test pulse. When the test pulse is doubled to 0.1 Hz, the attenuation is faster and occludes subsequent LTD. Attenuation of evoked responses by okadaic acid was also shown in other studies (Kourrich, et al, 2008). Previous studies also showed that application of non-selective phosphatase inhibitors calyculin A or microcystin-LR attenuated Purkinje EPSC (Ajima and Ito, 1995).…”
Section: Discussionsupporting
confidence: 73%